Measuring Women’s Control Over Assets - World Bank (World Bank, Washington, DC, 2021)
Gender inequalities in the ownership, control, and use of assets are a widespread and pervasive development challenge. Persistent gender gaps remain in women’s access to land, housing, and financial assets. Expanding women’s control over assets is key not only for improving gender equality, but also for promoting economic development and wellbeing. Researchers and policymakers have made important progress addressing many of the challenges posed by the heterogenous conceptualization of asset ownership across contexts. But knowledge gaps persist regarding the extent of women’s ownership and rights over assets, the nature and implications of gender differences in reporting data on property rights, and the best practices for questionnaire design and data collection protocols. This brief summarizes existing knowledge gaps in the three key measurement areas and lays out how the measures for advancing gender equality (MAGNET) initiative plans to tackle them. The ultimate goal is to generate rigorous empirical evidence to advise on the best tools to measure and analyze women’s control over assets.